2020
DOI: 10.1007/s00432-020-03333-4
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled estrogen receptor 1 (GPER-1) and agonist G-1 inhibit growth of ovarian cancer cells by activation of anti-tumoral transcriptome responses: impact of GPER-1 mRNA on survival

Abstract: Purpose The present study intended to further elucidate the role of G protein-coupled estrogen receptor 1 (GPER-1) in ovarian cancer by comparing the effects of a GPER-1 knockdown and treatment with its agonist G-1 on cell growth, apoptosis, and the transcriptome of two ovarian cancer cell lines. Furthermore, the role of GPER-1 in ovarian cancer survival was examined. Methods GPER-1 expression in OVCAR-3 and OAW-42 ovarian cancer cells was knocked down by RNAi. The effects on cell growth were measured by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…This confirms the assumption of a prognostically favourable effect of GPER-1 in studies of women with ER-positive BC [19,25]. GPER-1 has also been described as a favourable prognostic factor in earlystage cervical carcinoma, as well as in-vitro in ovarian cancer and in granulosa cell tumours [26][27][28]. Nevertheless, we did not find any association between GPER-1 status and the likelihood of relapse, but it should be taken into account that the statistical power of our study is lower than in most studies for FBC.…”
Section: Discussionsupporting
confidence: 77%
“…This confirms the assumption of a prognostically favourable effect of GPER-1 in studies of women with ER-positive BC [19,25]. GPER-1 has also been described as a favourable prognostic factor in earlystage cervical carcinoma, as well as in-vitro in ovarian cancer and in granulosa cell tumours [26][27][28]. Nevertheless, we did not find any association between GPER-1 status and the likelihood of relapse, but it should be taken into account that the statistical power of our study is lower than in most studies for FBC.…”
Section: Discussionsupporting
confidence: 77%
“… 14 These findings are consistent with our observations. However, Ignatov et al and Schüler‐Toprak et al demonstrated an association of GPER‐1 expression with favorable clinical outcomes and suppression of cell proliferation by G‐1, a selective GPER‐1 agonist 15 , 16 . The conflicting results in these studies mentioned above may arise from the application of different cell lines and different concentrations of the agonist.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Smith et al 13 showed an association of high GPER‐1 expression with a lower survival rate in patients with ovarian cancer, and Fujiwara et al found an association of both GPER‐1 expression and EGFR expression with poor outcomes in ovarian cancer. 14 In contrast, Ignatov et al 15 demonstrated a relation between low GPER‐1 expression and favorable outcomes in EOC, and Schuler‐Toprak et al 16 observed longer overall survival (OS) and progression‐free survival (PFS) in ovarian cancer patients with high mRNA expression of GPER‐1 using open‐access data. However, the association between GPER‐1 and patient survival in CCC has not been proved, probably because an extremely low number of patients with this histologic subtype were included in those previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…GPER has been proposed to act as tumor suppressor in ovarian cancer [ 105 ] and to have, together with Wnt pathway modulator Dickkopf 2 (Dkk2) expression, a positive prognostic impact in ovarian cancer patients [ 106 , 107 ]. GPER not only suppresses the proliferation of ovarian cancer cells by blocking tubulin polymerization [ 108 , 109 ], but its activation also led to a transcriptome response associated with growth inhibition in ovarian cancer cells [ 110 ] and triggered a ERK1/2-mediated trimethylation of Histone H3 at Lysine 4 (H3K4me3) to repress migration and proliferation in vitro [ 111 ]. However, contrasting evidence supports the role of GPER in mediating proliferation, migration, and invasion in vitro—through the expression of c-Fos, cyclin D1, Matrix Metallopeptidase 2 (MMP2, also known as gelatinase A, GELA or 72 kDa type IV collagenase) and MMP9 9 (also known as gelatinase B, GELB)—in both an E2-mediated [ 112 , 113 ] and a ligand-independent manner [ 114 ].…”
Section: Membrane Steroid Receptors and Their Role In Hormone-sensitive Cancersmentioning
confidence: 99%